A mathematical model used in flow lines for performance measurement and system improvement - Ang, Liu (2014)
The thesis is the extension of my previous work for the degree of Master of Engineering from MIT. My previous thesis is application-driven, aiming to improve overall performance of a flow line by optimization of existing facilities. And relevant proposals are on their way to implementation, expecting 10% increase in production rate and 18% decrease in inventory level. While this thesis focuses on more theoretical aspect of the problems: summarizing the establishment of the mathematical model, theoretical proof, programming and numerical experiment. The mathematical model developed in this thesis is particularly useful in system optimization of flow line by introduction of buffers. Given all the required raw data of the line, the programme can calculate key parameters of the line and priority of buffer locations. Together with analytical model or simulation, we can further determine the optimal buffer size at certain locations, in order to improve line performance. The method finds its industrial application in automated flow lines of a leading manufacturer of electronic appliances. (For confidentiality related issues, all the names are fabricated and all the data are disguised.)